Mint Essential Oils: Composition and Bioactivity - Ćavar Zeljković, Sanja (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
The essential oils of Mentha sp. are widely used as food, medicine, spices, and flavoring agents. Therefore, their chemical composition is an important parameter for assessing the quality of plants. Here, we summarize our recent findings on the chemical composition and biological activities of essential oils of selected mints i.e., Mentha aquatica 'Veronica', M. pulegium, M. x piperita, M. x piperita 'Bergamot', M. x piperita 'Citrata', M. x piperita 'Perpeta', M. x villosa, and M. microphylla, grown under the same environmental conditions. Since we have proved that the percentage content is not necessarily a reliable way of presenting the quality of the essential oil as a crop product that will be used in the food and pharmaceutical industry, the composition of these oils was also obtained by measuring the exact concentrations of each monoterpene that was found at a significant level. To characterize their pharmacological potential, essential oils were subjected to the testing of their abilities to reduce stable radicals, inhibit the activity of the enzyme tyrosinase – related to skin hyperpigmentation disorders, such as melanoma and age spots – but also their activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Among all tested oils, citrus-scented Mentha x villosa essential oil showed potent activity against free radicals, tyrosinase, and SARS-CoV-2. Although this species is not exploited as other mints (M. spicata, M. x piperita, M. arvensis), our findings show its potential for use in the food and pharmaceutical industry, especially due to its easy cultivation, which does not require pesticides.